Jurnal Pemasaran Event Education Fair Antologi Event & PRs Tahun 2022 oleh PT Meka Eduversity Komunikasi - Binta Fatihiyyah; Firman Syah (Bisnis Event, 2023)
MICE – Education Fair is an exhibition activity that displays types of education, both secondary education and higher education. This study aims to analyze elements of the marketing mix such as product, price, place, and promotion for marketing the 2022 Antologi Event & PRs Education Fair. This research was also conducted using the observation and interview methods of Antologi Event & PRs employees as the Event Organizer. The result of this study show that product, price, place, and promotions influence the marketing of the 2022 Education Fair Antologi Event & PRs event.Keyword: MICE, Marketing Mix, Education Fair.